Reorientação na diplomacia brasileira e o FOCEM: outra perspectiva sobre a integração regional - Pautasso, Diego (Meridiano 47 - Journal of Global Studies, 2017)
This article examines the importance of FOCEM as part of there orientation of Brazilian diplomacy under Lula’s government. This change in perspective policy has resulted in the expansion and deepening of regional integration in South America in the XXI century. In addition, the consolidation of Brazil’s leadership in the region strengthens its presence in international affairs.